Highly elastic medical sealants for flexible soft tissue
The surgical sealant was solved by using reactive hydrogel mixtures of electrophilic compounds, nucleophilic compounds and amphiphilic poly(alkyl)diol block polymers, combined with buffer solution, to form a high viscosity crosslinking sealant. The pleura repairs the problems of low viscosity and insufficient stretching ability, significantly improving sealing effect and biocompatibility.
Patent Information
- Application Number
- CN202380038506.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-06
- Filing Date
- 2023-05-02
- Publication Date
- 2024-12-27
AI Technical Summary
Existing surgical sealants have problems with low viscosity and insufficient stretching capacity when used for pleural repair, resulting in difficulty maintaining at the site of application and ineffective sealing, especially during dilation and contraction of the circulating lungs.
Using a reactive hydrogel mixture of electrophilic compounds and nucleophilic compounds, combined with amphiphilic poly(alkyl)diol block polymer and buffer solution, a high viscosity crosslinking sealant is formed, which increases the elasticity of the sealant and Tensile strength and further improve viscosity and cohesive properties by adding tackifiers.
The sealing effect of high viscosity and high tensile strength in pleural repair is achieved, which can effectively inhibit the outflow of sealant and maintain appropriate sealing, significantly improving the biocompatibility of sealant and drug delivery potential.
Smart Images

Figure CN119212740A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure describes liquid compositions for forming cross-linked bioabsorbable elastomeric sealants suitable for use in the repair of distensible soft tissue. Background Art
[0002] Cross-linkable mixtures of synthetic polymers and / or biologics are widely used as surgical sealants. These products typically begin with separate liquid components that will react with each other and form a strongly cross-linked gel when applied. The design of surgical sealants typically involves consideration of the mechanical properties of the delivery device and the mechanics of the sealant. Given the availability, the viscosity of the sealant is necessary to allow for the intended application of the sealant. The efficacy of the sealant is directly a consequence of the mechanics of the resulting gel, including tensile properties, adhesive properties, and burst pressure. For example, when used as a pleural sealant, elasticity is important for maintaining a durable and flexible seal during the expansion and contraction cycle of the lungs. There are several disadvantages to current commercial synthetic sealants. For example, Progel, an FDA-approved liquid sealant indicated for sealing pleural leaks, is a liquid sealant that is used to seal pleural air leaks. TM Possessing low viscosity, which makes it difficult to maintain the solution at the desired site of administration, and insufficient stretchability, which results in delamination from multiple surfaces during cyclic lung expansion.
[0003] One solution to low viscosity is to incorporate rheology modifiers, such as polysaccharides and natural gums, to increase the viscosity of the liquid sealant and thereby reduce the outflow of the liquid phase. Typically, viscosity modifiers are selected in such a way that they do not react with the active components of the sealant. As a result, these agents do not provide additional beneficial effects on the elasticity or cohesiveness of the resulting gel and, in some cases, may reduce elasticity due to adverse effects on mixing.
[0004]
[0006] Therefore, there is a need to provide a sealant for soft tissue that meets clinical needs for elasticity and strength, has improved handling characteristics including viscosity, and is able to withstand cyclic expansion and contraction. Summary of the invention
[0005] The present disclosure relates to compositions suitable for use as soft tissue sealants, and in particular as pleural sealants. To be used as clinically effective tissue sealants, the sealant composition must have a sufficiently high viscosity prior to curing to inhibit oozing out of the anatomical site to which it is applied, and exhibit sufficiently high tensile strength and elongation after curing to maintain an adequate seal and prevent delamination of the sealant from the anatomical site.
[0006] Thus, the present disclosure describes a liquid composition for forming a cross-linked sealant suitable for use in the repair of expandable soft tissue. The liquid composition according to the present disclosure is a reactive hydrogel mixture of an electrophilic compound and a nucleophilic compound, an amphiphilic poly(alkylene) glycol block polymer, and a buffer solution having a pH in the range of about 8.5 to about 10.5, wherein the electrophilic compound and the nucleophilic compound are capable of cross-linking with each other via a reaction of the available electrophilic and nucleophilic moieties of each compound. The electrophilic compound may include a polymer based on multi-arm polyethylene glycol (PEG), and the nucleophilic compound may include a multi-arm polymer containing at least one reactive amine group or thiol group. Preferably, the liquid composition includes a buffer solution having a pH in the range of about 8.5 to about 9.0.
[0007] The present disclosure describes improvements to biocompatible sealants, showing that the addition of amphiphilic poly(alkylene) glycol block polymers in modest amounts (<20% w / v) produces unexpected beneficial effects of increasing the viscosity of the liquid phase blend and improving the elasticity of the resulting hydrogel. The present disclosure describes further improvements to the above sealants by adding a viscosity enhancer, such that the unexpected and synergistic effects of the amphiphilic poly(alkylene) glycol block polymer and the viscosity enhancer produce improved viscosity, elasticity, adhesion and cohesive properties compared to conventional known biocompatible sealants. In addition to improved sealant tensile properties, the addition of amphiphilic poly(alkylene) glycol block polymers can provide beneficial effects in terms of drug delivery potential. Amphiphilic poly(alkylene) glycol block polymers have the ability to encapsulate and deliver hydrophobic drugs, and those abilities can be utilized in the liquid compositions described herein to provide therapeutic benefits to the target anatomical site of administration.
[0008] In certain embodiments, the amphiphilic poly(alkylene) glycol block polymer is present in the liquid composition in an amount of about 20% (w / v) or less of the liquid composition, such as, for example, in the range of about 5% to about 15% (w / v), or about 7.5% to about 12.5% (w / v). In another embodiment, the amphiphilic poly(alkylene) glycol block polymer comprises the base units of polyethylene glycol, polypropylene glycol, and copolymers thereof, such as, for example, a triblock copolymer comprising a central block of polypropylene glycol and two terminal blocks of polyethylene glycol (PEG).
[0009] In another embodiment, the liquid composition further comprises a viscosity enhancer, or a mixture of at least two different viscosity enhancers. In certain embodiments, the viscosity enhancer comprises at least carboxymethyl cellulose (CMC) or carrageenan. In certain other embodiments, the viscosity enhancer is present in the liquid composition in an amount ranging from about 0.1% to about 10% (w / v).
[0010] In certain embodiments, the electrophilic compound comprises at least one of 4-arm PEG-N-hydroxysuccinimide (PEG-NHS), or more specifically 4-arm PEG-succinimidyl glutarate (PEG-SG). In certain additional embodiments, the nucleophilic component comprises at least one of 4-arm PEG-amine or albumin.
[0011] The present disclosure also describes a system for forming a cross-linked sealant for use in repairing and treating soft tissue. According to certain embodiments, the system may include a first container containing a first liquid and a second container containing a second liquid, wherein the first liquid has a buffer solution with a pH in the range of about 8.5 to about 9.0, a cross-linkable electrophilic compound, and an amphiphilic poly(alkylene) glycol block polymer; and the second liquid has a buffer solution with a pH in the range of about 8.5 to about 9.0 and a cross-linkable nucleophilic compound, wherein the electrophilic compound and the nucleophilic compound are capable of cross-linking with each other via a reaction of the available electrophilic and nucleophilic portions of each compound. In the disclosed system, the cross-linkable electrophilic compound and the cross-linkable nucleophilic compound are configured to form a cross-linked soft tissue sealant when the first liquid and the second liquid are mixed. According to another embodiment, the first container may also include a tackifier as described above.
[0012] The present disclosure further describes a surgical method for treating or repairing soft tissue (e.g., pleural tissue), the surgical method comprising the steps of:
[0013] mixing a first liquid contained in a first container and a second liquid contained in a second container to form a liquid soft tissue sealant, wherein the first liquid comprises a buffer solution having a pH in the range of about 8.5 to about 9.0, a cross-linkable electrophilic compound, and an amphiphilic poly(alkylene) glycol block polymer; and the second liquid comprises a buffer solution having a pH in the range of about 8.5 to about 9.0, and a cross-linkable nucleophilic compound;
[0014] forming a liquid cross-linked tissue sealant from a mixture of the first fluid and the second fluid; and
[0015] Applying the liquid cross-linked tissue sealant to the pleural tissue to cover the target surface BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1A is a graphical representation of the ultimate extension of two different samples of the control sample and the control with the viscosity enhancer added;
[0017] Figure 1B yes Figure 1A A graphical representation of the ultimate extension of a control sample and a formulation according to the present disclosure comprising an amphiphilic poly(alkylene) glycol block polymer (Poloxamer 407);
[0018] Figure 1C Is from Figure 1B and additional samples including an amphiphilic poly(alkylene) glycol block polymer (Poloxamer 407) and a tackifier according to the present disclosure;
[0019] Figure 1D is Figure 1C Graphical representation of the ultimate stress of the sample measured in;
[0020] FIG. 2A to FIG. 2B is a graphical representation of the ultimate extension and ultimate stress of samples according to the present disclosure on various concentrations of an amphiphilic poly(alkylene) glycol block polymer (Poloxamer 407);
[0021] FIG. 3A to FIG. 3C is a graphical representation of limiting extension, limiting stress and stiffness shown as a fit for varying concentrations of electrophilic compound and amphiphilic poly(alkylene) glycol block polymer;
[0022] Figure 4 is a graphical representation of the dissolution times of samples according to the present disclosure;
[0023] Figure 5 is a graphical representation of polymerization times of samples according to the present disclosure;
[0024] Figure 6 is a graphical representation of sealant flow rate and stopping distance for samples according to the present disclosure;
[0025] Figure 7 is a box plot showing tensile test data with respect to elongation, maximum load, and stiffness for samples according to the present disclosure;
[0026] Figure 8 is a graphical representation of a load-extension curve of a tensile test of a sample according to the present disclosure;
[0027] Fig. 9 is a graphical representation of tissue adhesion at maximum load for a sample according to the present disclosure; and
[0028] Fig.10 is a box plot showing burst test data of samples according to the present disclosure. DETAILED DESCRIPTION
[0029] In this document, unless otherwise indicated, the term "one" or "a kind" is used to include one / kind or more than one / kind, and the term "or" is used to refer to a non-exclusive "or". In addition, it should be understood that the words or terms used herein are used only for descriptive purposes and not for limitation when not defined in another way. When expressing a range of values, another embodiment includes from a specific value and / or to other specific values. Similarly, when the value is expressed as an approximate value with "about" above, it should be understood that the specific value of the value constitutes another embodiment. All ranges include end values and can be combined. In addition, references to the values described in the range include every value in the range. It should also be understood that, for clarity, certain features of the present invention described herein in the context of a separate embodiment may also be provided in combination in a single embodiment. On the contrary, the various features of the present invention are described in the context of a single embodiment for simplicity, and may also be provided separately or in any sub-combination form.
[0030] As used herein, the phrase "consisting essentially of" is intended to limit the scope of a claim to include the recited components, compounds, substances, materials, or steps, and additionally include any components, compounds, substances, materials, or steps that do not materially affect the basic characteristics of the claimed invention.
[0031] The present disclosure describes a liquid composition for forming a cross-linked sealant suitable for use in the repair of distensible soft tissue. Preferably, the soft tissue is pleural tissue. The liquid composition according to the present disclosure is a reactive hydrogel mixture of an electrophilic compound and a nucleophilic compound, an amphiphilic poly(alkylene) glycol block polymer, and a buffer solution having a pH in the range of about 8.5 to about 9.0, wherein the electrophilic compound and the nucleophilic compound are capable of cross-linking with each other via reaction of the available electrophilic and nucleophilic moieties of each compound.
[0032] The electrophilic and nucleophilic reactive compounds that form the cross-linked structure of the hydrogel sealant are known in the art and can include synthetic polymers (such as multi-arm polyethylene glycol (PEG)-based polymers) and natural substances, and combinations thereof. Multi-arm PEGs suitable for use in the elastic layer may include 2, 3, 4, 6 or 8 multi-arm PEGs. In a preferred embodiment, the molecular weight of the multi-arm PEG is from about 2 kDa to about 40 kDa.
[0033] According to certain embodiments, the synthetic polymer may include a polymer with an activated ester, such as from the class of compounds of PEG-N-hydroxysuccinimide (PEG-NHS), PEG-aldehyde, PEG-acrylate, carboxyl-PEG, and 4-arm vinyl-PEG. According to another embodiment, a non-exhaustive list of suitable electrophilic compounds may include 4-arm-PEG-succinimidyl glutarate (SG), 4-arm-PEG-succinimidyl valerate, 4-arm-PEG-succinimidyl carbonate, 4-arm-PEG-succinimidyl succinate, 4-arm-PEG-succinimidyl butyrate, 4-arm-PEG-succinimidyl succinamide, 4-arm-PEG-succinimidyl propionate, 4-arm-PEG-sulfosuccinimidyl glutarate (SG), 4-arm-PEG-sulfosuccinimide 4-arm-PEG-sulfosuccinimidyl carbonate, 4-arm-PEG-sulfosuccinimidyl succinate, 4-arm-sulfosuccinimidyl butyrate, 4-arm-PEG-sulfosuccinimidyl succinamide, 4-arm-PEG-sulfosuccinimidyl propionate and 4-arm-PEG-isocyanate, 4-arm-PEG-imidate, 4-arm-PEG-maleimide, 4-arm-PEG-acetic acid, 4-arm-PEG-propionic acid, 4-arm-PEG-butyric acid, 4-arm-PEG-hexanoic acid and 4-arm-PEG-vinyl sulfone. Other examples include 2-arm, 3-arm, 6-arm and 8-arm-PEG of the exemplary 4-arm compounds listed above. As previously described, the electrophilic compound can include a blend of natural and synthetic components.
[0034] In certain embodiments, the nucleophilic compound comprises a natural compound, such as albumin, gelatin or collagen. In certain other embodiments, the nucleophilic compound may comprise a synthetic polymer, preferably a multi-arm polymer. In another embodiment, the nucleophilic compound contains at least one reactive amine group, such as, for example, a 4-arm PEG-amine or PEG-hydrazide, or a 4-arm PEG-thiol.
[0035] Suitable amphiphilic poly (alkylene) glycol block polymers according to the present disclosure include compounds from the class of polyether polyols, such as, for example, polyethylene glycol (PEG) and polypropylene glycol (PPG), and copolymers and mixtures thereof. In a preferred embodiment, the block polymer is a coblock polymer or a triblock polymer containing both PEG units and PPG units. For example, a suitable class of compounds is often referred to as poloxamer, and includes a triblock copolymer consisting of a central hydrophobic chain of PPG and two hydrophilic chains of PEG on both sides, the triblock copolymer consisting of a central hydrophobic block of polypropylene glycol and two hydrophilic blocks of polyethylene glycol (PEG) on both sides. Poloxamer is also often known by the trade name Pluronic. A particularly preferred embodiment is Poloxamer 407 (also referred to as Pluronic F127).
[0036] According to the present disclosure, the amphiphilic poly(alkylene) glycol block polymer is present in an amount of 20% (w / v) or less of the sealant composition; preferably, in the range of about 5% (w / v) to about 15% (w / v), and particularly preferably in the range of about 7.5% to about 12.5% (w / w) of the sealant composition.
[0037] In certain embodiments, the liquid composition according to the present disclosure consists essentially of a reactive hydrogel mixture of a cross-linkable electrophilic compound and a nucleophilic compound, an amphiphilic poly(alkylene) glycol block polymer, and a buffer solution having a pH in the range of about 8.5 to about 9.0. In a preferred embodiment, the liquid composition according to the present disclosure consists essentially of a triblock copolymer of PEG-NHS (e.g., 4-arm PEG-SG; 4-arm PEG-amine or albumin), a central block of PPG and two terminal blocks of PEG, and a buffer solution having a pH in the range of about 8.5 to about 9.0.
[0038] The disclosure also describes the preparation of the liquid composition as described above, which includes one or more tackifiers combined with the previously described amphiphilic poly (alkylene) glycol block polymer. Tackifiers are well known in the field of biocompatible sealants. Exemplary tackifiers may include, for example: carrageenan (iota, κ and λ), starch (including corn starch), cellulose (including carboxymethyl cellulose, hydroxypropyl methylcellulose, microcrystalline cellulose), alginate, agar (including agarose), glycerol, pectin (including apple pectin, citrus pectin), gum (including guar gum, gellan gum, xanthan gum, locust bean gum) and gelatin. According to certain embodiments, the tackifier includes a mixture of at least two different tackifier compounds. In another embodiment, the tackifier includes at least one of carboxymethyl cellulose (CMC) or carrageenan, and in yet another embodiment, includes a mixture of CMC and carrageenan.
[0039] According to an embodiment of the present disclosure, the tackifier is present in the composition in an amount ranging from about 0.1% to about 10% (w / v). In a preferred embodiment, the tackifier is present in the composition in an amount ranging from about 0.1% to about 5.0% (w / v). In yet another embodiment, the tackifier is present in the composition in an amount ranging from about 0.1% to about 1.0% (w / v). In a specific embodiment comprising a mixture of at least two tackifier compounds, at least one of the tackifier compounds is present in an amount ranging from about 0.1% to about 1.0%.
[0040] As previously described, in certain embodiments, at least two different viscosifiers can be combined for viscosity synergy, where the interaction with each other creates a new texture and accelerates thickening time. For example, when combined with starch, -carrageenan can increase the viscosity of a solution to ten times the viscosity of a solution with starch alone. These synergies can be very useful in liquid sealants according to the present disclosure because there are two benefits: 1) smaller concentrations of additives that exhibit synergy can be used, which can address potential toxicity issues of higher concentrations of a single additive; 2) smaller concentrations can also result in reduced costs.
[0041] Carrageenans are a family of high molecular weight linear polysaccharides composed of copolymers of galactose esters of sodium, potassium, magnesium and calcium sulfates and 3,6-anhydrogalactose. The viscosity of carrageenan solutions depends on molecular weight, concentration and temperature, as well as the presence of other solutes, with carrageenan viscosity generally increasing exponentially with concentration. There are three main types of carrageenans, corresponding to different degrees of sulfation: λ-carrageenan with three sulfate groups per disaccharide, l-carrageenan with two sulfate groups, and κ-carrageenan with one sulfate group. The higher ester sulfates require lower temperatures to dissolve the additives.
[0042] Although all three forms of carrageenan are water soluble, dissolution is affected by the type of carrageenan, counterions, solutes, temperature, and pH. λ-carrageenan is the most soluble of the three due to the level of sulfation; l-carrageenan is intermediate but appears hydrophilic because its two sulfate esters offset the less hydrophilic character of the 3,6-anhydrogalactose residues. Carrageenans are known to maintain good stability at neutral and alkaline pH, making them good potential additives for soft tissue liquid sealants that are typically composed of moderately alkaline buffers.
[0043] Starch (a linear chain of glucose units linked by glycosidic bonds) has limited solubility, which can pose problems for its use in standard sealant manufacturing processes. Isolated starch is virtually insoluble in cold water, alcohols, and most organic solvents due to hydrogen bonding and the crystalline nature of the molecule. In addition, aggregation readily occurs upon contact with water, as the polymer swells significantly. Temperature, pH, rate of heating, and the presence of other salts all affect starch. In addition, shear forces and pressure-induced mixing can alter the solubility of starch and its final viscosity. To help improve solubility, a small amount of starch can be added to water to gel or create a paste; dilution is then performed and more particles are slowly added to reach the desired concentration while heating.
[0044] Cellulose-derived carboxymethyl cellulose (CMC) consists of carboxymethyl groups bound to the hydroxyl groups of pyranose monomers along the cellulose backbone. The carboxymethyl groups act as an acid, making CMC an anionic polyelectrolyte. CMC is hydrophilic in nature and will swell in water, forming agglomerates and lumps. Shear forces applied during any mixing process involving CMC can affect the final viscosity of the solution. Dissolution rate and viscosity may also be affected by concentration and temperature; and pH and electrolytes may have a smaller effect. As temperature increases, viscosity decreases, although this is reversible, as the starting viscosity can be restored when the temperature returns to the starting value. CMC is stable over a wide range of pH values; only at levels greater than 11 will an effect be caused by alkaline hydrolysis, or at levels less than 4, where the cations will be replaced by hydrogen and cause the molecule to become insoluble in water. The effect of the electrolyte on viscosity depends on the ability of the cation to form a soluble salt with the molecule; this depends on the concentration of the salt and the CMC. When exposed to electrolytes, the CMC molecules will curl and change configuration, and thereby reduce viscosity.
[0045] Alginate is a water-soluble hydrophilic colloid biopolymer. It is an anionic polymer composed of a linear main chain of homopolymerized blocks of (1-4)-linked β-D-mannuronic acid (M) and its C-5 diastereomer α-L-guluronic acid (G) residues. Alginate dissolution usually requires active stirring and slow addition to the solvent to prevent caking and flocculation. Premixing with a liquid (such as alcohol or PEG) in which alginate is insoluble will enhance dispersion and promote dissolution. Concentration and temperature are expected to affect the dissolution and final viscosity of the solution. Shear rate also plays a role because alginate has pseudoplastic properties, in which viscosity decreases with increasing shear rate. Finally, alginate is highly sensitive to microbial attack than other carbohydrate-based additives, and if damaged, will result in reduced viscosity.
[0046] In certain embodiments, the liquid composition according to the present disclosure consists essentially of a reactive hydrogel mixture of an electrophilic compound and a nucleophilic compound, an amphiphilic poly(alkylene) glycol block polymer, a viscosity enhancer, and a buffer solution having a pH in the range of about 8.5 to about 9, wherein the electrophilic compound and the nucleophilic compound are capable of crosslinking with each other via reaction of the available electrophilic and nucleophilic moieties of each compound. In a preferred embodiment, the liquid composition according to the present disclosure consists essentially of a triblock copolymer including a central block of PPG and two terminal blocks of PEG, a mixture of CMC and iota-carrageenan, and a buffer solution having a pH in the range of about 8.5 to about 9.0.
[0047] The present disclosure also describes a system for forming a crosslinked sealant for use in repairing and treating soft tissue. According to certain embodiments, the system may include a first container containing a first liquid and a second container containing a second liquid, wherein the first liquid has a buffer solution with a pH in the range of about 8.5 to about 9.0, a crosslinkable electrophilic compound, and an amphiphilic poly(alkylene) glycol block polymer; and the second liquid has a buffer solution with a pH in the range of about 8.5 to about 9.0, and a crosslinkable nucleophilic compound. In the disclosed system, the crosslinkable electrophilic compound and the crosslinkable nucleophilic compound are configured to form a crosslinked soft tissue sealant when the first liquid and the second liquid are mixed.
[0048] The present disclosure further describes a surgical method for treating or repairing soft tissue (e.g., pleural tissue), the surgical method comprising the steps of:
[0049] mixing a first liquid contained in a first container and a second liquid contained in a second container to form a liquid soft tissue sealant, wherein the first liquid comprises a buffer solution having a pH in the range of about 8.5 to about 9.0, a cross-linkable electrophilic compound, and an amphiphilic poly(alkylene) glycol block polymer; and the second liquid comprises a buffer solution having a pH in the range of about 8.5 to about 9.0, and a cross-linkable nucleophilic compound;
[0050] forming a liquid cross-linked tissue sealant from a mixture of the first fluid and the second fluid; and
[0051] The liquid cross-linking tissue sealant is applied to cover the target pleural tissue surface.
[0052] Example
[0053] Example 1: Effect of the Ultimate Elongation and Ultimate Stress in a Modified Base Sealant Formulation (Biosynthetic) ring
[0054] Material:
[0055] Base formulation - 75 mg / mL 4 Arm PEG-SG-20k (electrophile), 10% albumin (nucleophile), 50 mM carbonate buffer, pH = 9.0
[0056] Additives - 0.1% i-carrageenan (thickener), 1% carboxymethylcellulose (thickener), 5% poloxamer 407 (amphiphilic polyalkylene glycol block polymer) (approximately MW = 12.6 kD).
[0057] In the first run, the ultimate extension was measured for three (3) samples of the base formulation versus two separate formulations containing tackifier compounds - four (4) samples containing the base formulation and 0.1% i-carrageenan, and five (5) samples containing the base formulation and 1.0% CMC.
[0058] In a second run, the extreme extension of ten (10) samples of the base formulation relative to three (3) samples containing the base formulation and 5% Poloxamer 407 was measured.
[0059] In a third run, the ultimate extension of ten (10) samples of the base formulation was measured relative to three (3) samples containing the base formulation and 5% poloxamer 407 and four (4) samples containing the base formulation, 5% poloxamer and 1% CMC / 0.2% i-carrageenan.
[0060] In the fourth run, the ultimate stress of ten (10) samples of the base formulation was measured relative to three (3) samples containing the base formulation and 5% poloxamer 407 and four (4) samples containing the base formulation, 5% poloxamer and 1% CMC / 0.2% i-carrageenan.
[0061] For this study, the sealants tested had a cure time of 10 minutes.
[0062] Ultimate stress, ultimate strain, and elastic modulus were calculated in MATLAB R2018. Statistical analysis was performed in Minitab v18. The tensile test measures the elongation at which the sealant completely fails when tested in the vertical tensile direction at 5 mm / min. Custom fixtures made of Teflon were designed to create a "dog bone" shape and press the sealants into it, which allows them to be mounted to an Instron Materials Tester. As the grips move vertically, the grips pull apart and the strength and elongation of each sample are measured. Failure is defined as the point at which the sealant completely fails within the fixture.
[0063] The results are shown in Figures 1A to 1D Reference Figure 1A, there were no statistically measurable differences in ultimate extension between the three formulations from the first run (2-sample t-test). Figure 1B In the second run, the ultimate extension was statistically different between the two groups (p=0.046, 2-sample t-test), showing an increase in the ultimate extension of the samples containing poloxamer 407. Figure 1C , similar to Figure 1B The results shown in , there is a statistically significant difference in ultimate extension between the base formulation and the two formulations containing poloxamer 407; however, there is no statistical change in ultimate extension between the two formulations with poloxamer 407 added with a viscosity enhancer (one-way ANOVA analysis). Finally, reference Figure 1D , there was a statistically significant increase in the ultimate stress of the test samples containing the tackifier compared to the two formulations without the tackifier (p=0.00, one-way ANOVA).
[0064] Example 2: Effect of varying the concentration of amphiphilic poly(alkylene) glycol block polymers on the performance of sealant formulations (biosynthesized) Influence of tensile properties
[0065] Pluronic F127 (amphiphilic poly (alkylene) glycol block polymer) [BASF trade name of poloxamer 407 previously described above] was dissolved in 100mM carbonate buffer (pH=8.0) at 0, 0.1, 0.3, 2, 5, 10, 15, 20, 25 and 30% (w / v). 5mL of Pluronic solution was added to 750mg PEG-SG4-20k and allowed to dissolve for 5 minutes. The solution was loaded into a 20mL syringe and attached to a 20mL syringe with 5mL of 20% albumin (dissolved in water) via a dual syringe connector. The solution was passed back and forth 10 times to produce a sealant. The sealant was immediately injected into the stretching mold for testing.
[0066] The tensile test measures the elongation at which the sealant completely fails when tested in the perpendicular tensile direction at 5 mm / min. Custom fixtures made of Teflon were designed to create a "dog bone" shape and press the sealants into it, which allows them to be mounted to an Instron Materials Tester.
[0067] As the grips move vertically, the clamps pull apart and the strength and elongation of each sample are measured. Failure is defined as the point at which the sealant completely fails within the clamps.
[0068] For this study, the cure time of the tested sealants was 10 minutes. Ultimate stress, ultimate strain, and elastic modulus were calculated in MATLAB R2018. One-way ANOVA was performed to provide statistical comparisons between groups.
[0069] refer to Figure 2A , there was a significant increase in the ultimate extension with increasing concentrations of Pluronic F127 (p < 0.01, one-way ANOVA, Appendix). Figure 2B , the ultimate stress (p<0.01, one-way ANOVA, Appendix) values increased to a maximum at approximately 10% concentration, and then subsequently decreased with increasing concentrations of Pluronic F127. Although the ultimate extension increased on average over the entire concentration range tested, the ultimate stress increased statistically between concentrations 5% and 15%, and was maximized between 7.5% and 12.5%.
[0070] Example 3: Effect of Amphiphilic Poly(alkylene) Glycol Block Polymer Concentration on Stretching of Sealant Formulations (Fully Synthesized) Impact of characteristics
[0071] Material:
[0072] Table 1
[0073] 4-ArmPEG-Amine-5k (mg / mL) 4-ArmPEG-SG-20k(mg / mL) Pluronic F127(mg / mL) 28.5 75 0 57.0 150 4 114.0
[0074] Utilize 3 factors, general factorial design in this study.PEG-amine is tested with 3 levels, and PEG-SG and Pluronic are tested with 2 levels.Pluronic F127 is dissolved in 100mM carbonate buffer (pH=8.0).5mL of Pluronic solution is added to 750mg PEG-SG4-20k and allowed to dissolve for 5 minutes.The solution is loaded into a 20mL syringe and attached to a 20mL syringe with 5mL of PEG-amine solution via a double syringe connector.The solution is passed back and forth 10 times to produce a sealant.The sealant is immediately injected into the stretching mold for testing.
[0075] The tensile test measures the elongation at which the sealant completely fails when tested in a vertical tensile direction at 5mm / min. Custom fixtures made of Teflon instead of aluminum are designed to create a "dog bone" shape and press the sealants into it, which allows them to be mounted to the Instron Materials Tester. As the grips move vertically, the clamps pull apart and the strength and elongation of each sample are measured. Failure is defined as the point at which the sealant completely fails within the fixture.
[0076] For this study, the cure time of the tested sealants was 10 minutes. The ultimate stress, ultimate strain, and elastic modulus were calculated in MATLAB R2018. Statistical analysis was performed in Minitab v18.
[0077] refer to FIG. 3A to FIG. 3C, the analysis of main effects showed that the ultimate extension of the formulation increased with decreasing PEG-SG and increasing Pluronic. The ultimate stress increased with increasing PEG-SG and increasing Pluronic. The stiffness increased with increasing PEG-SG and decreasing Pluronic. On the other hand, PEG-amine did not affect the tensile properties in a linear manner. As the concentration of PEG-amine increased from 28.5mg / mL to 57mg / mL, the properties did not change much; however, from 57mg / mL to 114mg / mL, the ultimate extension increased, and the ultimate stress and stiffness decreased significantly. The results show that PEG-SG, Pluronic and their interactions have a significant effect on the ultimate extension. PEG-amine and PEG-SG have a significant effect on the ultimate stress. PEG-amine, PEG-SG and Pluronic have a significant effect on stiffness.
[0078] Example 4: Analysis of Viscosity Enhancer Formulations
[0079] This study investigated individual viscosity enhancing additives and their combinations with control formulations while maintaining or improving functional material properties.
[0080] Materials - The components used in the formulations tested below are as follows:
[0081] PEG-SG (4 arms), MW: 20kDa, [Jenkem]
[0082] Bovine serum albumin, [Sigma A7030]
[0083] Sodium carbonate, [Sigma 223484]
[0084] ι-Carrageenan, [TCI C1805]
[0085] λ-Carrageenan, [TCI C3313]
[0086] Corn starch, [Ingredion]
[0087] Carboxymethylcellulose (CMC) sodium salt (HV), [Sigma C5013]
[0088] Alginate sodium salt from brown algae, [Sigma A2033]
[0089] F-127, [Sigma P2443]
[0090] Example 4A: Preparation of Liquid Sealant Set
[0091] Ten liquid sealant additive groups or additive combination groups were used in this study; the control condition without any additives consisted of PEG-SG4-20K. For each experimental group, at least three concentrations of the additive were first qualitatively evaluated for the ease with which they dissolved and produced / maintained enhanced viscosity in carbonate buffer (pH 9.0). Conditions that required excessively high temperatures (e.g., >5% starch), had undissolved solutes (e.g., >5% starch), or produced bubbles (e.g., >20% Pluronic F-127) were eliminated. Minor modifications to the experimental groups and / or additional controls were generated and used in different evaluations depending on the subgroup-goal. Table 2 below shows the sealant compositions prepared for testing.
[0092] Table 2 - List of formulations used for testing
[0093]
[0094] Example 4B: Evaluation of Dissolution
[0095] Additive and additive combination group are added to carbonate buffer to first evaluate the ease or difficulty of dissolving and compare in group.Produce a semi-quantitative scoring system from 1 to 3 to evaluate the number of steps; Score 1 indicates the process of 1 step, 2 represents 1-2 steps, and 3 represents>3 steps, which are shown in Table 3 below.As an example, 5% starch group has a score of 3, because dissolving needs to be slowly added to boiling carbonate buffer liquid solution by funnel, and the solution is in the motion / eddy current formed by agitator (3 step process requires particle wetting, rapid mixing and high heat).It is found that if directly added to carbonate buffer, all additives in this research can cause serious agglomeration and caking.For all additives (some additives are more than other additives), the gentle addition of single particle wetting, stirring / eddy, heating and / or time is necessary to a certain extent.Starch, CMC, alginate and any combination of starch mixed are the most labor-intensive and challenging for dissolving completely.In most cases, starch needs boiling temperature to dissolve completely, from the processing point of view, making it the poor choice of additive.
[0096] Table 3: Additive dissolution scores (1 = 1 step, 2 = 1-2 steps, 3 = > 2 steps)
[0097] sample Dissolution score ELS(control) 1 0.25% i-Carrageenan 2 5% starch 3 2% CMC 3 3% Alginate 3 0.25% i-carrageenan + 0.75% λ-carrageenan 2 0.25% i-carrageenan + 3% starch 3 0.75% λ-carrageenan + 1% CMC 2 0.75% λ-carrageenan + 1% alginate 2 10% F127 + 0.2% i-carrageenan + 1% CMC 2
[0098] Example 4C: Evaluation of Hydration ( Figure 4 )
[0099] PEG-SG4-20K powder is added to the carbonate buffer solution that viscosity increases to produce 150mg / mL solution.The solution is mixed via double syringe exchange using 5mL BD syringe and female-female connector.In order to assess the hydration time, record the number of pumps required for visually dissolving PEG as rate measurement.For consistency in measurement, only one operator performs the test and passes through each syringe at a rate of 1 pump / 2 seconds.Use virtual metronome as a guide to maintain accuracy.
[0100] The hydration time of PEG-SG4-20K powder in carbonate buffer with increased viscosity varied with the type of additives by double syringe exchange, which can be Figure 4 . The 3% alginate and 2% CMC conditions took the longest time (greater than 2 minutes). This time range may be problematic in a clinical setting. Unexpectedly, certain additive combinations such as 0.25% iota-carrageenan and .75% λ-carrageenan dissolved PEG relatively quickly despite showing high levels of dynamic viscosity.
[0101] Example 4D: Evaluation of polymerization
[0102] To extrude the actual sealant, the corresponding viscosity-enhanced 150 mg / mL PEG-SG4-20K solution and 20% bovine serum albumin (BSA) formulation were loaded into an Evicel delivery device attached to a prototype alternating viscous mixing tip. On a nutating rocker at 20 degrees, 1 mL of sealant was extruded into a 1" weigh boat containing 6 mm silicone beads. The time it took for the beads to stop moving reflected the polymerization time for the corresponding condition. This procedure was repeated for each condition (n=2). The results for each test sample are shown in Figure 5 middle.
[0103] In general, polymerization times were relatively reasonable for all adhesive sealant groups, as gelation was complete in 75 seconds or less. To provide appropriate clinical target times, preferably 30 seconds or less, some of these formulations may require additional modifications (e.g., concentration, pH changes, and mixing) to reduce polymerization times. For example, an additional 0.13% i-carrageenan formulation with a higher pH was tested in this experiment as a second control; the higher pH resulted in substantially faster polymerization, with an average time of 12.5 seconds. Without being bound by any particular theory, increasing pH may be a factor in reducing and controlling polymerization times.
[0104] Example 4E: Sealant Flow Rate, Stopping Distance, and Squeeze Out
[0105] Sealant flow rate and stopping distance provide important information about the flow properties of a viscous sealant. While reducing flow rate is the primary goal of a liquid sealant, a highly viscous sealant will be substandard (or ineffective) if additives significantly affect polymerization time (resulting in a greater stopping distance).
[0106] After loading the corresponding samples and 20% bovine serum albumin (BSA) into the Evicel delivery device attached to the prototype alternating viscous mixing tip, 2 mL of sealant was extruded in triplicate onto a 15 degree glass inclined plane (n=3). When the camera was positioned perpendicular to the surface of the inclined plane, the flow rate and distance were captured and calculated by photo and video, respectively. The flow rate is reported in inches per second, and the stopping distance is reported in inches (6 inches = maximum distance of the plane).
[0107] refer to Figure 6 , the viscosifier formulations had significantly lower flow rates compared to the control, however this did not result in correspondingly reduced stopping distances for those samples (each error bar was constructed using a 95% confidence interval for the mean sample size. n=3 for each group). Some sealant groups had high concentrations of viscosifier (e.g., 1% CMC), while having relatively higher viscosities, gradually flowing to longer distances. However, other formulations such as 2.5% starch performed poorly in both evaluations. Unexpectedly, formulations containing more than one viscosifier (each at relatively low concentrations) generally performed better because they produced very low flow rates without compromising polymerization, as reflected by the short stopping distances.
[0108] During the above test process, the extrusion force, thickness and tensile / strength of each formulation were semi-quantitatively evaluated on a scale of 1-3. When the extrusion force was based on tactile feedback, the thickness was measured at the top of the slope after the sealant was carefully separated from the glass. Tensile (elongation) and strength (breaking point resistance) are also tactile in nature and are qualitatively evaluated by hand after the sealant is carefully separated from the glass. For extrusion force and tensile / strength, 1 point is the lowest level and 3 points are the highest level. For thickness, a score of 1 indicates a measured value of <0.6 mm; a score of 2 is 0.6 mm to 1 mm; and a score of 3 is >1 mm. The results are shown in Table 3 below:
[0109] Table 4
[0110]
[0111] The extrusion force of various tackifier preparations and hydrogel thickness and stretching / strength provide important feature insights and differences with the control. The preparations with CMC and alginate (alone and in combination) have the highest extrusion force values. In some cases, this results in thicker coatings. Although qualitative, some of these groups also result in high stretching / strength. Unexpectedly, the preparations comprising F127 and tackifier have a stretching / strength degree that exceeds every other test preparation.
[0112] Example 4F: Tensile Properties of Viscous Liquid Sealants
[0113] When tested at 5mm / min in the vertical tensile direction, the tensile test measures the tensile strength and elongation at which the sealant fails completely. Custom fixtures are made of Teflon and are designed to create a "dog bone" shape to press the sealant into it, which allows them to be mounted on the Instron Materials Tester. Each of the viscous sealant groups is squeezed out in these fixtures using an Evicel delivery device attached to a prototype alternating viscous mixing tip for testing. When the chuck moves vertically, the fixture is pulled apart, and the strength and elongation of each sample are measured. Failure is defined as the point at which the sealant fails completely in the fixture. At least three samples (n>3) are tested in each group.
[0114] Tensile testing provides important distinctions and information about the biomaterial properties of viscous liquid sealants regarding elongation and stiffness. Figure 7 , a box plot of the results of tensile test data showing elongation, maximum load, and stiffness for the sample formulations. For elongation, the test revealed two groups that were different from the rest of the formulations: the "ι-carrageenan, 10K" and the "F127+CMC+ι-carrageenan" groups. The "ι-carrageenan, 10K" formulation did not perform well compared to the rest of the samples and had a significantly lower percent elongation at break. In contrast, the "F127+CMC+ι-carrageenan" formulation had a significantly higher percent elongation than the other formulations. To further illustrate this unexpected improvement, Figure 8 Comparative load-extension curves for all samples tested above are shown, with 3 samples from the group with F127 poloxamer showing unexpectedly significant superiority over the other formulations. Testing was performed sequentially for three samples of each group at 10 minutes of curing time, and then again after 10 minutes of curing time, which showed continued further improvement after curing. The "F127+CMC+iota-carrageenan" formulation had an average elongation higher than the control and the other formulations.
[0115] Example 4G: Tissue Adhesion Properties of Viscous Liquid Sealants
[0116] The tissue adhesion test measures the maximum adhesion load of the sealant between two tissue surfaces in the normal direction. The test is carried out according to ASTM F2258-05. Some modifications to the ASTM test protocol include a circular press plate (1 square inch area) and a 3mm gap between the two press plate surfaces: a porcine pleural sample (Farm to Pharm-Warren, NJ) is mounted to the platen, and the test fixture is mounted on the Instron Materials Tester. Each of the viscous sealant formulations is squeezed out in these fixtures using an Evicel delivery device attached to the prototype alternating viscous mixing tip for testing. The force between the two tissue surfaces is assessed using a low-capacity load cell. At the start of the test, the chuck of Instron moves in the vertical direction at a rate of 5mm / min until failure. The failure mode is defined as cohesive failure within the foam, or adhesive failure at the foam and tissue interface.
[0117] refer to Fig. 9 , the results of the tissue adhesion testing showed that the "iota-carrageenan, 10K", "iota-carrageenan + lambda-carrageenan", and "F127 + CMC + iota-carrageenan" performed at least 25% better than the ELS control. Although it was expected that the "iota-carrageenan, 10K" group would be able to withstand higher loads, given previous findings that sealant formulations with PEG-SG4-10K were stiffer, the other formulations contained additives that not only improved viscosity but also benefited tissue adhesion. As shown in Table 5 below, in almost all cases, the failure mode was cohesive. For the group with F127, it is important to note that the "o-ring failure" of the clamp occurred at a point where there was not even significant visible deformation at the tissue-sealant interface; this may indicate that the formulation was able to withstand even higher loads than recorded.
[0118] Table 5
[0119] Failure Mode ELS, no additives Cohesion / Partial bonding ι-Carrageenan Cohesion ι-Carrageenan, 10k Cohesion ι-Carrageenan, High pH Cohesion CMC Cohesion Alginate(DSE) Cohesion ι-Carrageenan + Starch Cohesion ι-Carrageenan + λ-Carrageenan Cohesion CMC+λ-carrageenan Cohesion Alginate + λ-carrageenan O-Ring Failure F127+CMC+ι-carrageenan O-Ring Failure
[0120] Example 4H: Burst Characteristics of Viscous Liquid Sealants
[0121] The burst test method measures the maximum burst pressure and failure mode of each formulation when applied to harvested porcine pleural samples. Pleural tissue was freshly harvested and provided by Farm to Pharm (Warren, NJ) before use. A single defect of 1 mm diameter was created in the mounted tissue sample and the air was purged before each application. -Each of the adhesive sealant groups was extruded in these fixture-holes using an Evicel delivery device attached to a prototype alternating viscous mixing tip for testing. Pressure was generated under the tissue surface using a syringe pump at an infusion rate of 2 ml / min and tested until failure. The failure peak pressure and failure mode of each sample were recorded. The failure mode was defined as cohesive failure within the sealant, or adhesive failure at the foam and tissue interface.
[0122] refer to Fig.10 , box plots show the maximum burst test. The results show the relatively high burst pressure of all preparations. It should be noted that "5% F127+0.1% iota-carrageenan+0.5% CMC" solution has a lower pH compared to other preparations. Based on the sample size and average comparison derived from the Tukey HSD method, all sample preparations with viscosifiers are at least equal to the control. "Alginate+λ-carrageenan" sample has a significantly high average burst pressure of 410.68mmHg, which is 105% of the control. When compared with "iota-carrageenan, 10K" and "iota-carrageenan+starch" preparations, the burst pressure of the preparation is also significantly higher. With reference to Table 6 below, different from what is seen in the tissue adhesion test (Table 5) above, the failure mode of tissue adhesion in the burst test shows a mixed situation of adhesion and cohesive failure. Interestingly, the control and preparations with F127 only have adhesion failure, while the samples with high concentrations of CMC and alginate only have cohesive failure.
[0123] The sealant formulations described herein not only exhibit enhanced overall viscosity, enabling retention at the site of application, but also benefit the cohesion of the crosslinked network of the sealant. Tensile evaluations demonstrate improvements in elastic strength without compromising other performance characteristics of the sealant. Additionally, the strain linearity of the hydrogel in proportion to the magnitude of applied stress demonstrates that the formulation can be readily tailored to meet the compliance of various body tissues while improving overall handling characteristics. As shown and described above, the sealant formulations according to the present disclosure demonstrate high potential for utilizing the effective performance and applicability of a variety of known biocompatible crosslinking reactants, thereby benefiting both patients and surgeons.
Claims
1. A liquid composition for forming a cross-linked sealant for an expandable soft tissue, the liquid composition comprising: a reactive hydrogel mixture comprising an electrophilic compound and a nucleophilic compound, wherein the electrophilic compound comprises a multi-arm polyethylene glycol (PEG) based polymer, and wherein the nucleophilic compound comprises at least one reactive amine group, and wherein the electrophilic compound and the nucleophilic compound are capable of cross-linking with each other via reaction of available electrophilic and nucleophilic moieties of each compound; an amphiphilic polyalkylene glycol block polymer, the amount of the amphiphilic polyalkylene glycol block polymer being 20% (w / v) or less of the sealant composition; and a buffer solution having a pH in the range of about 8.5 to about 10.5; wherein the composition has a final crosslinked hydrogel phase having an ultimate elongation in the range of about 15 mm to about 40 mm and an ultimate tensile stress in the range of about 2.4 kPa to 5.9 kPa.
2. The liquid composition according to claim 1, wherein The buffer solution has a pH in the range of about 8.5 to about 9.
0.
3. The liquid composition according to claim 1 or claim 2, further comprising a viscosity increasing agent.
4. The liquid composition according to claim 3, wherein The viscosity enhancing agent includes at least one of carboxymethyl cellulose (CMC) or carrageenan.
5. The liquid composition according to any one of claims 3 or 4, wherein The tackifier comprises a mixture of at least two different tackifier compounds.
6. The liquid composition according to claim 5, wherein The viscosity increasing agent is a mixture of carboxymethyl cellulose (CMC) and carrageenan.
7. The liquid composition according to any one of claims 3 to 6, wherein The viscosity increasing agent is present in the composition in an amount ranging from about 0.1% to about 10% (w / v).
8. A liquid composition according to any one of the preceding claims, wherein The electrophilic compound includes PEGN-hydroxysuccinimide activated ester (PEG-NHS).
9. The liquid composition according to claim 8, wherein The PEG-NHS is PEG-succinimidyl glutarate (PEG-SG).
10. A liquid composition according to any one of the preceding claims, wherein The nucleophilic compound comprises at least one of 4-arm PEG-amine or albumin.
11. The liquid composition according to any one of the preceding claims, wherein the amphiphilic polyalkylene glycol block polymer comprises base units of polyethylene glycol, polypropylene glycol and copolymers thereof.
12. The liquid composition according to claim 11, wherein The amphiphilic poly(alkylene) glycol block polymer comprises a triblock copolymer comprising a central block of polypropylene glycol and two terminal blocks of polyethylene glycol (PEG).
13. A liquid composition according to any one of the preceding claims, wherein The amphiphilic polyalkylene glycol block polymer is in the range of about 5% to about 15% (w / v) of the sealant composition.
14. The liquid composition according to claim 13, wherein The amphiphilic polyalkylene glycol block polymer is in the range of about 7.5% to about 12.5% (w / v) of the sealant composition.
15. A system for forming a cross-linked sealant for an expandable soft tissue, the system comprising: a first container containing a first liquid having a buffer solution having a pH in the range of about 8.5 to about 9.0, a cross-linkable electrophilic compound, and an amphiphilic poly(alkylene) glycol block polymer; as well as a second container containing a second liquid having a buffer solution having a pH in the range of about 8.5 to about 9.0 and a cross-linkable nucleophilic compound; Wherein the cross-linkable electrophilic compound and the cross-linkable nucleophilic compound are configured to form a cross-linked soft tissue sealant when the first liquid and the second liquid are mixed.
16. The system of claim 15, wherein: The first container also includes a viscosity increasing agent.
17. The system of claim 16, wherein: The viscosity enhancing agent includes at least one of carboxymethyl cellulose (CMC) or carrageenan.
18. A system according to any one of claims 16 or 17, wherein: The viscosity increasing agent is present in the composition in an amount ranging from about 0.1% to about 10% (w / v).
19. A system according to any one of claims 15 to 18, wherein: The amphiphilic polyalkylene glycol block polymer comprises base units of polyethylene glycol, polypropylene glycol and copolymers thereof.
20. The system of claim 19, wherein: The amphiphilic poly(alkylene) glycol block polymer comprises a triblock copolymer comprising a central block of polypropylene glycol and two terminal blocks of polyethylene glycol (PEG).
21. A system according to any one of claims 15 to 20, wherein: The amphiphilic polyalkylene glycol block polymer is in the range of about 5% to about 15% (w / v) of the sealant composition.
22. The system of claim 21, wherein: The amphiphilic polyalkylene glycol block polymer is in the range of about 7.5% to about 12.5% (w / v) of the sealant composition.
23. A method of treating or repairing soft tissue, comprising: mixing a first liquid contained in a first container and a second liquid contained in a second container to form a liquid soft tissue sealant, wherein the first liquid comprises a buffer solution having a pH in the range of about 8.5 to about 9.0, a cross-linkable electrophilic compound, and an amphiphilic poly(alkylene) glycol block polymer, and the second liquid comprises a buffer solution having a pH in the range of about 8.5 to about 9.0 and a cross-linkable nucleophilic compound; forming a liquid tissue sealant from a mixture of a first fluid and a second fluid; applying the liquid tissue sealant to cover the target pleural tissue surface; as well as The liquid tissue sealant is allowed to cross-link on the targeted pleural tissue surface.
24. A liquid composition for forming a cross-linked sealant for an expandable soft tissue, the liquid composition consisting essentially of: a reactive hydrogel mixture comprising a multi-arm polyethylene glycol (PEG)-based polymer having at least one reactive electrophilic group and a multi-arm polymer containing at least one reactive amine group; an amphiphilic poly(alkylene) glycol block polymer, wherein the amount of the amphiphilic poly(alkylene) glycol block polymer is 20% (w / v) or less of the liquid composition; a viscosity increasing agent in a range of about 0.1% to about 10% (w / v); and a buffer solution having a pH in the range of about 8.5 to about 9.0; in; and Wherein, as measured relative to a comparative liquid composition having the reactive hydrogel mixture and the buffer solution in the absence of the amphiphilic poly(alkylene) glycol block polymer, the ultimate extension value and the ultimate stress value of the liquid composition after cross-linking are greater than the ultimate extension value and the ultimate stress value of the comparative liquid composition after cross-linking when measured under the same conditions.
